(untitled) (Research, Society and Development, 2021)
Humanity is going through a technological movement never seen before, in which information and communication reach an essential level in people’s lives. Among the technological innovations, computer simulations stand out, which can be conceptualized as the construction and operational manipulation of a model, that is, a physical or symbolic representation of aspects of a physical or social process. Computer simulation is applied in health courses to teach clinical techniques and procedures, including various objects: games, anatomical models, mannequins, dolls, case studies, and multimedia presentations. Simulations facilitate the acquisition of skills for patient care, providing the immersion of students in safe interactive environments to develop the health process. In this sense, this article aims to conduct an exploratory and bibliographic study on the use of computer simulation for teaching and learning in health courses, highlighting the main benefits of this technology in colleges in the 21st century.